1994
DOI: 10.1111/j.1525-1446.1994.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Home Care Nursing Resources by the Elderly

Abstract: We explored the influence of nursing dependency over and above sociodemographic factors and medical conditions on the use of home care nursing resources by patients 65 years of age and older. Use measures were number of visits made by home care nurses, and length of nursing stay. Nurses' reports, direct observation of nursing care provided, patient interviews, and record abstraction were used to obtain data on 236 patients who were admitted to and discharged from a certified public home health agency. Nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The demographics of the two groups were comparable. A cardiac condition was the most frequent diagnosis in this study; as has been reported in other studies of community dwelling seniors (Esposito, 1992;Helberg, 1994). The larger proportion of women to men in this age range and marital status of the subjects are also consistent with the literature on home care and aging (Dellaseger & Stricklin, 1993;Glick, 1994;Health and Welfare Canada, 1992;Kempen & Suurmeijer, 1991;Statistics Canada, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…The demographics of the two groups were comparable. A cardiac condition was the most frequent diagnosis in this study; as has been reported in other studies of community dwelling seniors (Esposito, 1992;Helberg, 1994). The larger proportion of women to men in this age range and marital status of the subjects are also consistent with the literature on home care and aging (Dellaseger & Stricklin, 1993;Glick, 1994;Health and Welfare Canada, 1992;Kempen & Suurmeijer, 1991;Statistics Canada, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…19-23 One of the findings was that an increase in the number of nursing problems was associated with higher resource use. 19, 22 Helberg’s study 21 also supported the relationship between increased nursing interventions and resource utilization. Other studies focused on predicting outcomes.…”
Section: Introductionmentioning
confidence: 79%
“…NANDA‐I nursing diagnoses were associated or significantly predictive for the nursing workload in hospital medical and surgical setting (Halloran, 1985; O'Brien‐Pallas et al, 1997), while both NANDA‐I and OS nursing diagnoses were associated or significantly predictive for the length and/or number of nursing care visit in home care (Hays, 1992; Helberg, 1994; Marek, 1996; Morales‐Asencio et al, 2009; O'Brien‐Pallas et al, 2001).…”
Section: Resultsmentioning
confidence: 99%